A Decision Support System for Prioritizing Inventory Procurement Using the MOORA Method with ROC Weighting - Adinda Ramadhani; Sopia Juliyanti Hutajulu; Edward Robinson Siagian; Fince Tinus Waruwu (Jurnal Armada Informatika, 2026)
Inventory management at the Frisian Flag Distributor requires a system capable of determining procurement priorities accurately and objectively. Inaccurately determining which items should be prioritized often leads to problems such as overstock, understock, and the risk of losses due to expired goods. To address these issues, a decision support system using the MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis) method with ROC (Rank Order Centroid) weighting was implemented. ROC weighting is used to determine the importance of each criterion based on priority order, while the MOORA method is used in the normalization process, calculating optimization values, and determining alternative rankings. The criteria used in the decision-making process include sales level, remaining stock, market demand, product price, and expiration date. Data processing results show that the combination of the MOORA and ROC methods can produce a systematic, measurable, and objective order of stock procurement priorities. The designed system can assist distributor management in making faster and more accurate decisions. The implementation of this method is expected to improve inventory management efficiency and minimize the risk of losses due to errors in determining procurement priorities.